X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=hints%2Fassignment_4_hint_3_alternate_1.mdwn;h=f0b720cd0d21b46c70c06bf2a39a241f559a7f44;hp=900c6cb16327ad8ac03ca0cf4b4ce645e21a154b;hb=004782ebd72fdb95badbaef55d2faaa6c49f3bed;hpb=f4c96076c1abbdf13bfb90d7e5b56ebe80dd7de7 diff --git a/hints/assignment_4_hint_3_alternate_1.mdwn b/hints/assignment_4_hint_3_alternate_1.mdwn index 900c6cb1..f0b720cd 100644 --- a/hints/assignment_4_hint_3_alternate_1.mdwn +++ b/hints/assignment_4_hint_3_alternate_1.mdwn @@ -11,15 +11,46 @@ Alternate strategy for Y1, Y2 is implemented using regular, non-mutual recursion, like this (`u` is a variable not occurring free in `A`, `B`, or `C`): - let rec u g x = (let f = u g in A) - in let rec g y = (let f = u g in B) - in let f = u g in + let rec u g x = (let f = u g in A) in + let rec g y = (let f = u g in B) in + let f = u g in C or, expanded into the form we've been working with: - let u = Y (\u g x. (\f. A) (u g)) in - let g = Y (\g y. (\f. B) (u g)) in - let f = u g in + let u = Y (\u g x. (\f. A) (u g)) in + let g = Y ( \g y. (\f. B) (u g)) in + let f = u g in C + We abstract the Y1 and Y2 combinators from this as follows: + + let Yu = \ff. Y (\u g. ff ( u g ) g) in + let Y2 = \ff gg. Y ( \g. gg (Yu ff g ) g) in + let Y1 = \ff gg. (Yu ff) (Y2 ff gg) in + let f = Y1 (\f g. A) (\f g. B) in + let g = Y2 (\f g. A) (\f g. B) in + C + + +* Here's the same strategy extended to three mutually-recursive functions. `f`, `g` and `h`: + + let v = Y (\v g h x. (\f. A) (v g h)) in + let w = Y ( \w h x. (\g. (\f. B) (v g h)) (w h)) in + let h = Y ( \h x. (\g. (\f. C) (v g h)) (w h)) in + let g = w h in + let f = v g h in + D + + Or in Y1of3, Y2of3, Y3of3 form: + + let Yv = \ff. Y (\v g h. ff ( v g h) g h) in + let Yw = \ff gg. Y ( \w h. (\g. gg (Yv ff g h) g h) ( w h)) in + let Y3of3 = \ff gg hh. Y ( \h. (\g. hh (Yv ff g h) g h) (Yw ff gg h)) in + let Y2of3 = \ff gg hh. Yw ff gg (Y3of3 ff gg hh) in + let Y1of3 = \ff gg hh. Yv ff (Y2of3 ff gg hh) (Y3of3 ff gg hh) in + let f = Y1of3 (\f g h. A) (\f g h. B) (\f g h. C) in + let g = Y2of3 (\f g h. A) (\f g h. B) (\f g h. C) in + let h = Y3of3 (\f g h. A) (\f g h. B) (\f g h. C) in + D +